(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Unconventional writing surfaces are also unusual surfaces. Forensic Document Examiners come across the variety of cases , commonly the usual surfaces or writings on conventional surfaces, but the cases with writings on unconventional surfaces are also being encountered frequently. Writings with unconventional writing instruments are also being received in forensic laboratories. Writings on unconventional surfaces with unconventional writing instruments are usually found in cases such as murder, suicide, robbery, to threaten, to defame etc . These cases pose several challenges for Forensic Document Examiner because of the type of surface or the type of writing instrument. In this paper we will discuss the challenges which Forensic Document Examiner faces while examining such cases.